2015
DOI: 10.1136/tobaccocontrol-2015-052510
|View full text |Cite
|
Sign up to set email alerts
|

Associations between lifetime tobacco exposure with infertility and age at natural menopause: the Women's Health Initiative Observational Study

Abstract: Active smoking and SHS exposure are associated with increased risk of infertility and natural menopause occurring before the age of 50 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
43
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 42 publications
7
43
1
2
Order By: Relevance
“…Many previous studies, including a meta-analysis, have confirmed that exposure to cigarette smoke is a risk factor for early menopause [23,32,33]. This conclusion was further supported by our study.…”
Section: Discussionsupporting
confidence: 91%
“…Many previous studies, including a meta-analysis, have confirmed that exposure to cigarette smoke is a risk factor for early menopause [23,32,33]. This conclusion was further supported by our study.…”
Section: Discussionsupporting
confidence: 91%
“…Fifth, no data on secondhand smoking was available in our study, despite the fact that it has been shown to influence fertility. 37 Separate analyses were conducted for women and men as a significant ( p=0.001) interaction was found between gender and smoking status regarding the number of children and age at first birth, and also because it would have been difficult to justify an adjustment on contraception in men. Still, we conducted a joint analysis in men and women, the results of which are summarised in online supplementary table S4; the results were comparable to those reported separately for each gender, that is, no association with the number of children but lower age at first birth among current smokers.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Parity and breastfeeding variables are generally reported to have good validity in the NOWAC Study . Missing information on age at menopause was treated according to smoking status, as women who smoke have been shown to have earlier menopause . Mean age at menopause for current and former smokers in our study (49 and 50 years, respectively) was used to complete missing data for participants who were current or former smokers.…”
Section: Methodsmentioning
confidence: 99%